MONITORING THE EFFECTIVENESS OF FINANCING A CLUSTER OF OIL AND GAS AND CHEMICAL EQUIPMENT MANUFACTURERS OF THE VORONEZH REGION - O. D. Gaisha (Вестник университета)
The form of integration of subjects as a cluster, in particular a cluster of producers of oil and gas and chemical equipment of the Voronezh region, which is a form of Association of interconnected companies in a certain territory, including scientific and technical and industrial enterprises, universities and research centers, has been considered. The experience of developed countries demonstrates the use of the cluster concept as an effective tool that contributes to improving the competitiveness of individual regions where clusters are based, as well as the country as a whole, and the development of individual economic sectors and participating enterprises. Within the framework of this study, the process of financial control of the Voronezh region cluster has been reviewed, and also implementation and efficiency of financing of the cluster of oil and gas and chemical equipment manufacturers have been analysed. As a result of the analysis, the strengths and weaknesses of the cluster have been revealed. Within the framework of research, the methods of bibliographic and logical analysis, systematic approach have been used.